Fresno County Women Lawyers' Installation of Officers Dinner Meeting - Watkins, Howard::::::::: (1988)
ALJ Ivy Roberts, Christine Goodrich and Ruth Lind; in background: Judges Herbert Levy, Sandra Snyder-Hylton, and Armando Rodriguez